Manifestations of Psychological Alienation Among Syrian University Youth "A Field Study upon A Sample of Students of Tishreen University" - Kahileh, Reem; Deeb, Juhaina (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aims to reveal the extent of the manifestationspsychological alienation among university youth, and the effect of gender, marital status and accommodation on the level of psychological alienation phenomenon. This research was applied on (110) university students from Tishreen University. To achieve this goal the following tool was used: psychological alienation scale by the researcher after reviewing the previous studies, the scale includes (Normlessness, Powerlessness, Aimlessness, Meaninglessness) dimensions. The results showed thatThe most prevalent manifestations of psychological alienation was normlessness, followed by powerlessness, then aimlessness, and finally meaninglessness. the prevalence of psychological alienation phenomenon among university students is by (57.27%). The results didn't show statistically significant differences between the study sample in the level of psychological alienation phenomenon according to gender, marital status, and accommodation variables.